Changes in inoculated Salmonella enterica subsp. enterica Serovar Enteritidis and other microbiological qualities of vacuum-packed carrot slices after treatment with aqueous extract of Lobularia maritima - Ben Hsouna, Anis; Čmiková, Natália; Ben Akacha, Boutheina; Ben Saad, Rania; Mnif, Wissem; Garzoli, Stefania; Kačániová, Miroslava (Heliyon, 2024)
After harvesting, pathogens can infect fresh vegetables in different ways. Pathogenic bacteria associated with fresh vegetables can cause widespread epidemics associated with foodborne illness. The aim of this study was to assess the microbiological quality of carrot slices after treatment with aqueous extracts of Lobularia maritima (AELm) at different concentrations AELm1 (10 mg/mL), AELm2 (5 mg/mL), AELm3 (2.5 mg/mL) and AELm4 (1.25 mg/mL), and Salmonella enterica subsp. enterica serovar Enteritidis, along with vacuum packaging and storage of carrots for 7 days at 4 °C. On days 1. and 7., total viable counts (TVC), and coliforms bacteria (CB), and Salmonella count were all analysed. Microorganisms that were obtained from carrots were identified using MALDI-TOF MS Biotyper Mass Spectrometry. The total viable, coliform bacteria and Salmonella counts were varied by the group of treatment. Higher counts were found in the control group on both days. The most isolated species of bacteria were Salmonella enterica and Pantoea agglomerans on the 1. day and Klebsiella oxytoca on the 7. day. The current study adds useful information for a better understanding of how Salmonella enterica reacts to the effect of AELm and its potential use as a sustainable washing method to eliminate bacteria from freshly cut carrots.